(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
The purpose of this study was to analyze the mathematical creative thinking abilities of sixth-grade MI students through the Collaborative Problem Solving model of flat shape material as an effort to improve fluency, flexibility, and novelty in problem solving. This research method applies a qualitative approach with a case study design using eight learning groups, namely two heterogeneous groups, two high homogeneous groups, two medium homogeneous groups, and two low homogeneous groups. Data were obtained through problem-solving tests, observations, interviews, focus group discussions, and documentation, which were then analyzed using the Miles and Huberman interactive model, covering the stages of data reduction, data presentation, and conclusion drawing. The research findings show that heterogeneous groups display the most optimal creative thinking abilities because they are able to consistently produce many diverse ideas, strategies, and new solutions. Highly homogeneous groups also showed good creative performance, especially in fluency and novelty, but their strategic flexibility was relatively limited. Moderately homogeneous groups were in the moderately creative category with developing idea variation, while low homogeneous groups produced fewer ideas and strategies. These findings confirm that appropriate grouping in CPS plays an important role in optimizing the development of creative thinking.